2019
DOI: 10.1038/s41598-019-39810-1
|View full text |Cite
|
Sign up to set email alerts
|

Mutational convergence acts as a major player in adaptive parallel evolution of Shigella spp.

Abstract: Shigella spp., emerging from multiple origins of Escherichia coli , poses a significant health threat as a causative agent of bacillary dysentery. While multiple serotypes of four different species have evolved via independent lineages, Shigella spp. are designated as a single pathotype, primarily because of their common mode of pathogenesis. Convergent horizontal transfer events have so far been attributed to the commonalities in the evolution of virule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…As the ecological distinctness of the clade II strains were preliminary at this stage, we guided the model with inclusion of other Escherichia genomes that has exhibited traits of adaptation to one of the habitats. Such genomes included S. dysenteriae from the Shigella genus, which is essentially a lineage of E. coli that had evolved from multiple E. coli lineages to become highly specialized human pathogens through convergent evolution involving independent horizontal gene transfers and gene losses [35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the ecological distinctness of the clade II strains were preliminary at this stage, we guided the model with inclusion of other Escherichia genomes that has exhibited traits of adaptation to one of the habitats. Such genomes included S. dysenteriae from the Shigella genus, which is essentially a lineage of E. coli that had evolved from multiple E. coli lineages to become highly specialized human pathogens through convergent evolution involving independent horizontal gene transfers and gene losses [35].…”
Section: Discussionmentioning
confidence: 99%
“…To minimize the inclusion of genes that were phylogenetic markers rather than informative of phenotype, we included another three more distantly related genomes, i.e., Shigella dysenteriae Sd197, E. coli ECOR66 (both gastrointestinal), and Escherichia clade IV TW14182 (environmental). Previous studies on these genomes showed evidences of adaptations to either external environment or gastrointestinal habitats for the genomes [3,21,22,[31][32][33][34][35][36]. Functional importance of sequence variations were scored using the DBS metric by comparing the protein coding genes of each strain to the profile HMMs of Gammaproteobacterial proteins (gproNOG.hmm) from the eggNOG database (http://eggnogdb.embl.de/).…”
Section: Random Forest Classifier Constructing and Trainingmentioning
confidence: 99%
“…(Gluck‐Thaler et al, 2020 ) as well as in the emergence of multiple dysentery‐causing Shigella spp. (Thomas et al, 2019 ). For bacterial plant pathogens, one trait of major economic and scientific interest is host specificity.…”
Section: Introductionmentioning
confidence: 99%
“…In these cases, the excess of beneficial mutations produced by the mutator clones drives them to a high frequency within the population, and the presence of a mutator allele can therefore be considered a signature of sustained adaptation. (iii) Genomic studies of epidemic bacterial clones and experimentally evolved laboratory strains ( 11 ) have revealed convergence at a molecular level ( 12 , 13 ) that can be seen as a hallmark of adaptation. Among all the possible mutations that may occur, finding mutations with comparable effects reflects the filtering action of natural selection.…”
Section: Introductionmentioning
confidence: 99%